ガレクチン7を標的とした中耳真珠腫診断薬の開発 - 羽藤, 直人; 茂木, 正樹; 竹政, 絵理香; 鈴木, 康之; 劉, 爽 (日本薬理学会年会要旨集, 2022)
Aiming at complete excision of cholesteatoma during trympanomastoidectomy and therefore reducing the risk of recurrence, the current study was undertaken to develop a seed DNA-aptamer-based fluorophore-probe, which targets human galectin-7, as an intraoperative lesion-identifying indicator for the surgical treatment of cholesteatoma. A galectin-7-targeted DNA-aptamer library was generated for labeling the cholesteatoma matrix using cell-based systematic evolution of ligands by an exponential enrichment technique. The binding characteristics of the identified aptamers were analyzed, and structure optimization of the identified aptamers was carried out both in silico and in vitro. Using galectin-7-aptamer guided molecular imaging, the excision margins of cholesteatoma matrix and surrounding normal tissue were successfully observed in a xenografted cholesteatoma model. It is highly expected that specific galectin-7-aptamers could progress to future clinical trials for both imaging and therapeutic applications and therefore benefit cholesteatoma patients.